New records of Pteris (Pteridaceae) from the Neotropics - Rojas Alvarado, Alexander (2014)
As a result of studies on neotropical Pteris L., we report new records of Pteris albertiae and P. longifoliafrom Costa Rica; P. longipetiolulata from Costa Rica, Panama, Peru, Bolivia, and Venezuela; and P. muricatopedatafrom Mexico and Guatemala. The expanded distribution range and addition of species to biodiversity lists provide relevant information about the ecology and taxonomy of the species.